Revegetation research 1976 progress report Sub-Projects VE 7.2, 7.3, and 7.4 ... - Vaartnou & Sons Enterprises Ltd. (University of Alberta Library, 1977)
Laboratory studies were conducted during 1976 to investigate native grasses and legumes potentially useful for revegetation on various soils. Plant growth was tested in various soils with and without the addition of fertilizer in the greenhouse and ill growth chambers. The Genera tested were: Agropyron Alopecurus, Bromus, Calamagrostis, Festuca, Phalaris, Phleum, Poa, Puccinellia, Astragalus, Hedysarum, Lupinus, Oxytropis, Glycyrrhiza, Lathyrus, Thermopsis, and Vicia. Field studies were conducted at Woodbend Station, Devon. Germination and early establishment were observed on unscarifled, fall-planted and scarified, spring-planted legumes. Work was begun at the Alberta Environment Research Station at Vegreville. Native grasses, naturalized grasses, agricultural varieties of grasses, and native and agricultural varieties of legumes were planted to be evaluated in the uniformity garden. Ft Fort McMurray, research areas were partly established on the Great Canadian Oil Sands Ltd. tailings dike site and the ...